Financial Management Practices Of Msmes: A Case Study Of Jangun Marning Business In Bulukumba, South Sulawesi, Indonesia - Agusdiwana Suarni; Chindy Putri Ardhana; Sahabuddin N (IECON: International Economics and Business Conference, 2024)
This study aims to analyze the financial management practices of micro, small, and medium enterprises (MSMEs) in Bulukumba, South Sulawesi, Indonesia. The context of this study is based on the challenges faced by MSMEs in managing their finances, which often lead to difficulties in business planning and development. The methodology adopted in this study is qualitative, using in-depth interview techniques with business owners and using source triangulation for data analysis. The findings of the study show that many MSME owners do not have a formal financial plan, which has an impact on cash flow management and future planning. In addition, they lack the courage to invest in modern technologies that can improve productivity. The conclusions of this study highlight the importance of financial education and applied technology to improve the financial management practices of MSMEs, which in turn can support their desire to support businesses.